Is it possible to talk about violence climate in grassroots sport? A study on the psychosocial adaptations of young athletes - Juan González-Hernández; Manuel Gómez-López; Gustavo Carlo; David Manzano-Sánchez (Frontiers in Psychology)
IntroductionThere is a need for greater scientific attention to research on violence (e.g., insults, intimidation, beatings) in contexts where such behaviors are prevalent. The agonizing win-lose vision that oftentimes is characteristic of sports competition is not understood in the same way in grassroots sports as in professional sports. Although increasingly frequent, the federative systems for young athletes replicate professional competitions, and the agonizing win-lose vision and psychosocial agents that characterize sports competitions do not impact grassroots sports in the same way as in professional sports. The present study aimed to establish a predictive model of the influence of exposure to violence in initiation sports on peer social relations under competitive situations in young athletes.MethodThrough a descriptive, non-randomized, and associative study, a sample of 503 young athletes (Mage = 14.76 1 ± 72 years; 54.80% girls) was recollected, belonging to different Spanish sports centres who completed instruments designed to identify their exposure to violence, prosocial and aggressive tendencies among peers, and competitiveness.ResultsThe results show that increased exposure to violence in sports amplifies those effects that excessive motivation for success and external influences, increases the likelihood of aggressive behaviors in young athletes (mainly in boys), while the emergence of prosocial skills in both boys and girls reduces aggressiveness and exposure to violent behaviors.DiscussionFor this reason, to offer a more than relevant background in reducing the effects of excessive competitiveness in grassroots sport, scientific contributions on the protective efficacy of prosocial tendencies against the emergence of aggressive behavior. In addition, contemplating the sociological analysis of the proliferation of insults, harassment, and violent behavior (e.g., observed behaviors or victimization) experienced in sports at very early ages will allow, in a more applied vision, the convenience of designing more psycho-educational sport practice strategies (e.g., social skills integrated into sports action, fair play) both for young athletes and for those adults who accompany them (e.g., parents, coaches, managers).ConclusionAddressing the effects of excessive competitiveness and violence in grassroots sports requires a comprehensive approach involving both sociological analysis and applied psycho-educational interventions.